PELAKSANAAN PERJANJIAN KREDIT USAHA TANI KOPERASI UNIT DESA (KUD) PETAPAHAN MAKMUR SEJAHTERA - Evandre Arif Nanda; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The credit agreement is an agreement between the Debtor with the creditor konsensuil who delivered accounts payable relationship, where the Debtor is obligated to repay the loan granted by the creditor, based on the terms and conditions agreed upon by the parties. In the implementation of the agreement many agreements are not performing well so need legal protection.The purpose of this study is to investigate the implementation of the credit agreement have to farm village unit cooperatives (KUD) Petapahan Makmur Sejahtera. To find out why the event of default under the credit agreement farming in the Village Unit Cooperatives (KUD) Petapahan Makmur Sejahtera and how the settlement efforts in the implementation of the savings and loan defaults in the Village Unit Cooperatives (KUD) Petapahan Makmur Sejahtera.This type of research adlah sociological research. This research was conducted in the Village Unit Cooperatives (KUD) Petapahan Makmur Sejahtera village Petapahan Kampar, Sedangkang sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data terseier , data collection techniques in this study with interviews, questionnaires, and literature study.Farmer Business Credit Agreement implementation in the Village Unit Cooperatives (KUD) Petapahan Makmur Sejahtera has not done well. Because of the default committed by the debtor and the creditor. Cooperative efforts made to resolve the breach in the implementation of savings and loans in the Village Unit Cooperatives (KUD) Petapahan Makmur Sejahtera is giving SP I, SP II, SP III, immediately come to the place of the debtor, seek a solution amicably settlement, sell or foreclose credit guarantees.Keywords: Agreement-Credit-Tort